Intergrative Human Capital Model: Emperical Evidence at the Central Statistics Agency in Aceh Province - Fitri Aswin Aswin; Ichsan Ichsan Ichsan; Naufal Bachri Bachri (Faculty of Economics and Business, Universitas Malikussaleh, 2021)
The purpose of this study is to examine the effect of human capital, compensation and work discipline on the performance of the employees for the Central Statistics Agency in Aceh Province and to determine whether the job satisfaction mediates relationships. The data used are primary data by distributing questionnaires to 200 employees for the Central Statistics Agency for Regencies in Aceh Province. The data analysis technique in this study used Structural Equation Modeling (SEM) which was operated through the Amos software. The results showed that human capital, compensation and work discipline can increase job satisfaction and employee performance. Likewise, job satisfaction is direct and significant on employee performance. In addition, the job satisfaction variable also partially mediates the effect of human capital and compensation on performance and the influence of work discipline on the performance of the employees for the Aceh Province Central Statistics Agency. This study shows that the need for human capital in shaping the performance of employees in government